PERBANDINGAN RETINAL GANGLION CELL THICKNESS DAN PERIMETRI PASIEN DIABETES MELITUS TIPE 2 - sherly muchlis muchlis; Ardizal Rahman; Weni Helvinda (Universitas Fort De Kock, 2020)
Diabetic retinopathy (RD) is a microvascular complication that often occurs in diabetes mellitus (DM). Retinal ganglion cells (RGC) are reduced in the early stages of DM, even before microvascular abnormalities are seen on the retina. Methods: Sample of 35 eyes of non RD RD type 2 patients and 35 mild non proliferative diabetic retinopathy (NPDR) eyes After examination of ophthalmological status, perimetry and optical coherence tomography (OCT) were examined. Results: The mean MD on non-RD type 2 DM -2.74 ± 3.5 mild NPDR -5.61 ± 4.5 with p value 0.414. The average non-RD type 2 PSD DM was -3.35 ± 3.3, mild NPDR was 4.16 ± 1.4 with a p value of 0.206. The mean RGC thickness of patients with non-RD type 2 DM was 83.8 ± 7.4 µm, mild NPDR 82.7 ± 8.1 μm. There was a decrease in the value of RGC thickness, MD and PSD in patients with type 2 DM, but it was not statistically significant . Conclusion: No significant difference was found in RGC thickness in DM patients between non-RD and mild NPDR. No significant difference was found between MD and PSD in DM patients between non-RD and mild NPDR. No significant relationship was found between RGC thickness and perimetry in DM patients between non-RD and mild NPDR.